Endogenous Purinergic Control of Bladder Activity via Presynaptic P2X(3) and P2X(2/3) Receptors in the Spinal Cord - Kaan, Timothy K. Y. (Society for Neuroscience, 2010)
P2X(3) and P2X(2/3) receptors are localized on sensory afferents both peripherally and centrally and have been implicated in various sensory functions. However, the physiological role of these receptors expressed presynaptically in the spinal cord in regulating sensory transmission remains to be elucidated. Here, a novel selective P2X(3) and P2X(2/3) antagonist, AF-792 [5-(5-ethynyl-2-isopropyl-4-methoxy-phenoxy)-pyrimidine-2,4-diamine, previously known as RO-5], in addition to less selective purinoceptor ligands, was applied intrathecally in vivo. Cystometry recordings were made to assess changes in the micturition reflex contractions after drug treatments. We found that AF-792 inhibited micturition reflex activity significantly (300 nmol; from baseline contraction intervals of 1.18 ± 0.07 to 9.33 ± 2.50 min). Furthermore, inhibition of P2X(3) and P2X(2/3) receptors in the spinal cord significantly attenuated spinal activation of extracellular-signal regulated kinases induced by acute peripheral stimulation of the bladder with 1% acetic acid by 46.4 ± 12.0% on average. Hence, the data suggest that afferent signals originating from the bladder are regulated by spinal P2X(3) and P2X(2/3) receptors and establish directly an endogenous central presynaptic purinergic mechanism to regulate visceral sensory transmission. Identification of this spinal purinergic control in visceral activities may help the development of P2X(3) and P2X(2/3) antagonist to treat urological dysfunction, such as overactive bladder, and possibly other debilitating sensory disorders, including chronic pain states.